Geochemistry in the Critical Zone: limestone-shale and kimberlite weathering in the Flint Hills, Kansas, USA - Gura, Colleen Marie (Kansas State University, 2017)
The Critical Zone is the realm where rocks meet life. This study examines the physicochemical interactions that occur when interbedded limestone-shale systems and kimberlitic rocks weather to form soils. Fast weathering processes with extensive soil loss have been a major environmental concern in the Flint Hills for decades. Knowledge of soil formation processes, rates of formation and subsequent loss, and understanding how these processes differ in different systems are critical for managing soil as a resource. Kimberlites are CO₂-rich igneous rocks that are high in Mg and Fe; they are compositionally distinct from the Paleozoic limestones and shales found throughout the rest of the region. This study will compare the geochemistry and mineralogy of the Stockdale Kimberlite in Riley county to that of interbedded limestone-shale system typical of the Flint Hills as sampled from Konza Prairie LTER. Bulk composition and mineralogy of the soils overlying these different bedrock types have been analyzed using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), bulk elemental extractions, and particle size analyses. Results show that the kimberlitic soils have higher concentrations of Fe, Mg, Ca, K and some trace elements in greater proportions (e.g. Ti, Ni, Cu). The weathering products differ mineralogically as well, e.g. lizardite is abundant in kimberlitic soils and absent from the limestone terranes. Kimberlite derived soils also contain minerals as well such as kleberite (an alteration product of illminite), phlogopite, and magnetite. Kimberlite-sourced soils have different physical properties than the thin limestone-sourced soils surrounding them. Particle size analysis shows that the limestone-shale soils have different proportions of the clay size fraction in different core locations (~47% in highlands, ~51% at watershed base, ~41% in lowlands) whereas kimberlitic soils have a larger sand fraction than Konza (~19% vs. 10%). Clay minerals from the limestone-shale system reveals clay micas, kaolinite, and some expandable 2:1 layer silicates. Clay minerals from kimberlite-sourced soils are identified as primarily smectites with clay micas and kaolinites. Similarities between the kimberlite and limestone-shale soils are primarily seen in the shallower portions of the soil profile, suggesting that loess/wind-blown dust make a significant contribution to the soils in both areas. It could be concluded that kimberlite-sourced and limestone-shale-sourced soils produce weathering products that differ both chemically and mineralogically and could potentially have agricultural significance in terms of water retention as well as ionic and nutrient mobilities in these soils.
Keywords: Geochemistry; Limestone; Kimberlite; Critical zone; Weathering; Shale